2013
DOI: 10.1097/id.0000000000000011
|View full text |Cite
|
Sign up to set email alerts
|

Bone Grafts Using Autogenous Tooth Blocks

Abstract: There were no notable complications associated with the bone transplant materials. The AutoBT block is clinically useful for a variety of bone grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
34
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 14 publications
3
34
0
2
Order By: Relevance
“…Such porosity can influence the osteoconductive characteristics of the scaffold by creating spaces for osteoblast attachment, differentiation, and growth and vascular invasion from surrounding tissues [Figure 4]. [21] Recently, Kabir et al . [22] reported that perforated root dentin matrix blocks with artificial macropores (1 mm in diameter) contributed to active bone ingrowth in critical-size bone defects of the iliac crest in adult sheep.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such porosity can influence the osteoconductive characteristics of the scaffold by creating spaces for osteoblast attachment, differentiation, and growth and vascular invasion from surrounding tissues [Figure 4]. [21] Recently, Kabir et al . [22] reported that perforated root dentin matrix blocks with artificial macropores (1 mm in diameter) contributed to active bone ingrowth in critical-size bone defects of the iliac crest in adult sheep.…”
Section: Discussionmentioning
confidence: 99%
“…[21] The alveolar bone volume was well maintained both vertically and horizontally, and the formed bone was not resorbed during the early stages. Histological examination showed aponeurotic fusions between the gingiva and the DDM block, osteocytic embedding, osteoclastic resorption, and vascular invasion into the DDM block.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the properties of healing, ABTB has almost same composition with autologous bone such as Type I collagen, minerals and several proteins [14,19,20]. Structurally, ABTB has 0.2-0.3 mm diamter macropores to enhance vascular invasion from the host tissues and 3-5 µm diameter micropores for exchanging proteins between host tissues and dentin matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al reported that the osteoinductive and osteoconductive functions of ABTB were verified by histological examination [19,[20][21][22]. Kim et al also reported in the long term follow up study of ABTB that CBA, which were 41.78% in the mandible and 28.28% in the maxilla, appear to be closely related to decreases in BH because his phenomenon was mainly caused by a reduction in BH (17.03% in the maxilla and 40.8% in the mandible) rather than ARW (21.18% in the maxilla and 24.61% in the mandible) [23].…”
Section: Discussionmentioning
confidence: 99%
“…20,21 And then AutoBT materials were commercialized in 2008, many researches have been presented and positive results have been reported in clinic. [22][23][24][25][26][27][28] In a study of x-ray diffraction (XRD), the XRD pattern of the autogenous tooth bone graft material was similar to that of autogenous bone. 29 In an analysis of the inorganic component, the autogenous tooth bone graft material identified as low crystalline hydroxyapatite, which is similar to the minerals of human bone.…”
mentioning
confidence: 99%